2016
DOI: 10.17221/132/2015-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical traits of red-fleshed, commercial and ancient apple cultivars

Abstract: Contessa C., Botta R. (2016) Cultivation of apples is currently based on a limited number of commercial cultivars; as a consequence, ancient and local varieties have almost completely disappeared. Red-fleshed, ancient and commercial cultivars were analysed for flesh firmness, soluble solid content, pH, titratable acidity, total phenolics and anthocyanin contents, total antioxidant capacity, sugars and organic acids composition, to evaluate their nutraceutical value. The ancient cultivars, in particular cv. Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
4
20
3
Order By: Relevance
“…Also, results from more studies reported that clones (genotypes) of the 'Red Delicious' group had smaller to moderate TA contents (Koukourikou-Petridou et al, 2007;Ahmed et al, 2013;Milošević et al, 2018). In general, our range of TA values was within the range determined by other researchers (Sasnauskas et al, 2007;Nour et al, 2010;Contessa and Botta, 2016).…”
Section: Data Insupporting
confidence: 86%
See 2 more Smart Citations
“…Also, results from more studies reported that clones (genotypes) of the 'Red Delicious' group had smaller to moderate TA contents (Koukourikou-Petridou et al, 2007;Ahmed et al, 2013;Milošević et al, 2018). In general, our range of TA values was within the range determined by other researchers (Sasnauskas et al, 2007;Nour et al, 2010;Contessa and Botta, 2016).…”
Section: Data Insupporting
confidence: 86%
“…The comparison of the TPC and TFC values obtained in the present study with those of other studies suggests similar trends although differences in the units used and analytical methods employed make a direct comparison difficult (Drogoudi et al, 2008). For example, the edible part of peeled apple fruits contained TPC between 31.42 and 90.12 mg GAE 100 g -1 fw (Contessa and Botta, 2016), whereas Kähkönen et al (1999) reported 12 mg GAE 100 g -1 dw in the flesh of an unspecified cultivar. However, higher contents of phenolic compounds in the peel than the flesh were also reported by other researchers (Wolfe et al, 2003;Chinnici et al, 2004;Leccese et al, 2009;Milošević et al, 2018).…”
Section: Data Insupporting
confidence: 77%
See 1 more Smart Citation
“…Apple titratable acidity values in various researches range from 0.18 to -0.52 g malic acid equivalent 100 mg -1 in different commercial and red-fleshed apple cultivars [Vieira et al 2009a, Piagentini andPirovani 2017], while the value of the titratable acidity of apple used in our research was 2.21 g malic acid equivalent 100 g -1 FW. Similarly, the pH values of apples determined in most research works falls between 3.05 and 4.25 [Rupasinghe et al 2010, Vieira et al 2009a, Wu et al 2007, Contessa and Botta 2016, but in Malus floribunda coccinella fruit, the pH value was found to be 2.89. Table 2 represents the organic acids and sugars found in Malus floribunda coccinella fruit.…”
Section: Some Physical and Physicochemical Properties Of The Fruitmentioning
confidence: 90%
“…The value of malic acid determined in our research was found to be 25.394 g kg -1 FW. However, the value of malic acid identified in commercial apples in other researches varies between 0.5-18.9 g kg -1 [Ma et al 2015, Contessa andBotta 2016]. Therefore, it can be concluded that the concentration of malic acid in Malus floribunda coccinella fruit is higher than the other apples used in various studies.…”
Section: Some Physical and Physicochemical Properties Of The Fruitmentioning
confidence: 91%